Preparation of Porous Scaffold Based on Poly(3-hydroxybutyrate-co-3-hydroxyvalerate-co-3-hydroxyhexanoate) and FucoPol - Pereira, João Ricardo (2023)
project LA/P/0140/202019 of the Associate Laboratory Institute for Health and Bioeconomy-i4HB. Publisher Copyright: © 2023 by the authors.